Proyecto de factibilidad para la producción y comercialización de aliño de piña, en la ciudad de Loja. - Álvarez Jiménez, Erika Del Cisne (2024)
The feasibility project was carried out with the purpose of evaluating the feasibility of a new product in the market, objectives were established such as; market study which included the demand, supply and unsatisfied demand, as well as the development of a marketing plan; a technical study was conducted to determine the size, location and engineering of the project, the organizational study to define the legal and administrative structure; The research has a quantitative approach, the deductive method was used, the research was exploratory and descriptive, with a non-experimental design for which various techniques and instruments were used to collect information; after analyzing the demand and supply, it is considered that the unsatisfied demand for the first year is 523,429 units, the capacity used is 116,480 units, the investment required to start up the enterprise is $ 60.230,42, the production cost for the first year is $ 77.669,17 with a retail price of $ 1.00, which will generate sales revenue of $ 116.503,75, the break-even point is 32% of the installed capacity and $ 37.463 based on sales, and the following evaluation indicators were applied: Net Present Value (NPV) of $ 65.823,65 which is a positive NPV; Internal Rate of Return (IRR) of 45,31 %; Capital Recovery Period in 2 years, 4 months and 28 days; Benefit-Cost Ratio of 1.50 and Sensitivity Analysis (SA) supporting a cost increase of 16 % and a decrease in income of 11 %. It is concluded that the project is feasible.